Assessment of Rifampicin Resistance in Presumptive Tuberculosis Cases at Dadeldhura Hospital of Sudurpaschim Province of Nepal - Madan Singh Bohara (RADS Journal of Biological Research & Applied Science)
Objectives: This study sought to determine the prevalence of rifampicin-resistant tuberculosis (RR-TB) and Mycobacterium tuberculosis (MTB) in patients at Dadeldhura Hospital in Nepal who were suspected of having pulmonary tuberculosis. The study's primary objectives were to assess the prevalence of MTB and RR-TB and to identify related sociodemographic variables.